Hubungan Tingkat Stres dengan Kualitas Hidup Pasien Tuberkulosis di Puskesmas Perumnas II Pontianak, Indonesia: Hasil Penelitian - Sakila, Shella; Fitriangga, Agus; In’am Ilmiawan, Muhammad (PT Kalbe Farma Tbk., 2025)
Introduction: Tuberculosis patients need long-term treatment. The effects of anti-tuberculosis drugs and stigma in society may cause stress, which can decrease the patient’s quality of life. This research aims to search for the correlation between stress level and quality of life in tuberculosis patients in Puskesmas Perumnas II Pontianak. Methods: An analytical study with a cross-sectional approach was conducted in January 2021 at Puskesmas Perumnas II Pontianak. The total sampling technique acquired 24 respondents. Analysis was performed using the Spearman rank correlation test. Results: The stress level was 83.3% in normal stress, 8.3% mild stress, 8.3% moderate stress, 79% of respondents had a good quality of life, and 21% of respondents had a poor quality of life. The Spearman rank correlation test results showed no significant correlation between stress level and quality of life (p=0,195). Conclusion: No significant correlation between stress level and quality of life in tuberculosis patients in the Puskesmas Perumnas II Pontianak.